Case report: Childhood erythrocytosis due to hypermanganesemia caused by homozygous SLC30A10 mutation - Coppola, Tiziana; Hughes, Hannah; Finch, Paul T.; Hess, Joshua A.; Wu, Steve; Prada, Carlos E.; Miethke, Alexander G.; Zhang, Wenying; Kalfa, Theodosia A. (Frontiers in Hematology, 2024)
We present a rare case of erythrocytosis due to a homozygous SLC30A10 mutation, causative of Hypermanganesemia with Dystonia, Polycythemia, and Cirrhosis (HMDPC). The patient presented at 7 years of age with the incidental finding of hemoglobin up to 22.3 g/dL. Despite extensive phenotypic evaluation and genetic testing for common causes of erythrocytosis, etiology remained unknown for 1.5 years until whole exome sequencing revealed the genetic diagnosis. Upon neurological evaluation, the patient was found to have very mild dystonia due to manganese deposition in the basal ganglia, midbrain, and cerebellum, as seen in brain MRI. Chelation with trientine orally was initiated, which led to resolution of his erythrocytosis along with decrease of Mn deposition in brain tissues. Recurrence of erythrocytosis occurred after 4 years due to inappropriately stored trientine and iron deficiency. This required the temporary addition of intravenous calcium disodium edetate to his treatment regimen. This case illustrates the development of secondary erythrocytosis due to hypermanganesemia leading to manganese deposition in the hepatocytes, causing a sense of tissue hypoxia and stimulating erythropoietin production. It also shows the competition between manganese and iron for absorption in the body. Moreover, it demonstrates the importance of broad genetic evaluation for the diagnosis of ultra-rare diseases. In this case, timely diagnosis and initiation of appropriate treatment prevented irreversible damage to the brain and liver with a profound improvement on his prognosis.